Concentrations of perfluoroalkyl and polyfluoroalkyl substances and blood glucose in pregnant women - Yanfeng Ren; Longmei Jin; Fen Yang; Hong Liang; Zhaofeng Zhang; Jing Du; Xiuxia Song; Maohua Miao; Wei Yuan (BMC, 2020)
Abstract Background Evidence on the association between exposure to perfluoroalkyl and polyfluoroalkyl substances (PFASs) and blood glucose concentrations in pregnant women is inconsistent. This study aimed to examine the association between PFAS exposure and the concentrations of fasting plasma glucose (FPG) and one-hour plasma glucose (1 h-PG) after a 50-g oral glucose tolerance test in pregnant women. Methods The study was based on the Shanghai-Minhang Birth Cohort, in which 1292 pregnant women were recruited. Among them, 981 women provided blood samples (at 12-16 gestational weeks) for PFAS measurement. FPG data collected from 856 women at 12-20 GW and 1 h-PG data collected from 705 women at 20-28 GW were obtained through medical records from the routine prenatal care system. High FPG or 1 h-PG was defined as ≥90th percentile of FPG or 1 h-PG. The analysis of eight PFASs was conducted in this study: perfluorohexane sulfonate (PFHxS), perfluorooctane sulfonate (PFOS), perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA), perfluoroundecanoic acid (PFUdA), perfluorododecanoic acid (PFDoA), and perfluorotridecanoic acid (PFTrDA). The odds ratios (ORs) and associated 95% confidence intervals (CIs) were estimated to determine the associations of each PFAS compound with high FPG and 1 h-PG from a logistic regression model. Results After adjustment for potential confounders, most PFASs were positively associated with high 1 h-PG concentrations. The OR for high 1 h-PG concentrations was 1.87 (95% CI: 1.15-3.05) with a one log unit increase of PFOS; similar associations were observed for PFNA (OR: 2.15, 95% CI: 1.24-3.74), PFDA (OR: 1.61, 95% CI: 1.10-2.44), PFUdA (OR: 1.71, 95% CI: 1.12-2.62), and PFDoA (OR: 1.34, 95% CI: 1.00-1.81). When the PFAS concentrations were categorized into three groups by tertiles, the highest tertiles of PFOS, PFOA, PFNA, PFDA, PFDoA, and PFTrDA had a statistically significant increase in the risk of high 1 h-PG concentrations compared with the lowest tertiles. No statistically significant association was observed between PFAS exposure and high FPG. Conclusion PFAS exposure was associated with an increased risk of high 1 h-PG among pregnant women, but no such association was observed for FPG.